(untitled) - Marcelo Campos Moraes Amato; João Flávio Gurjão Madureira; Ricardo Santos de Oliveira (Arquivos de Neuro-Psiquiatria)
Objectives:To determine the clinical presentation and treatment outcome of pediatric intracranial cavernous malformation (CM) in a single-centered institution. Methods:Clinical data review of 30 patients under 18 years-old who had undergone surgery for cavernous malformation from January 1993 to December 2011. Results:The Study Group included 18 males and 12 females (mean age: 8.7 years-old). Symptoms at presentation were seizures (16/30, 53.3%), headache (15/30, 50.0%), and focal neurological deficits (11/30, 36.6%). Multiple cavernous malformations were found in 5/30 (16.6%). According to location, patients were classified in groups: (G1) brain-steam in 5/30 (16.6%), (G2) cerebellum in 2/30 (6.6%), (G3) supratentorial associated with seizures in 16/30 (53.3%), and (G4) supratentorial without seizures in 7/30 (23.3%). Surgical resection was performed in 26 out of 30 (86.6%) patients. The mean follow-up period was 4.1 years. Of 15 children followed-up with preoperative seizures, all were rendered seizure-free after surgery. Conclusions:For symptomatic solitary cavernous malformation, the treatment of choice is complete microsurgical excision preceded by careful anatomical and functional evaluation. For multiple cavernous malformation or asymptomatic patients, the treatment modalities must be cautiously considered. Objetivos:Determinar a apresentação clínica e o acompanhamento do tratamento em crianças com angioma cavernoso intracraniano numa única instituição.Métodos:Revisão de dados clínicos de 30 pacientes menores de 18 anos com que passaram por uma cirurgia de angioma cavernoso intracraniano entre janeiro de 1993 a dezembro de 2011.Resultados:O grupo de estudo incluiu 18 sujeitos masculinos e 12 femininos (idade média: 8,7 anos). Os sintomas iniciais eram convulsões (16/30, 53,3%), cefaleia (15/30, 50,0%) e déficits neurológicos focais (11/30, 36,6%). Havia angiomas cavernosos intracranianos múltiplos em 5 de 30 (16.6%). A classificação foi feita em grupos de acordo com a localização: (G1) tronco cerebral em 5/30 (16,6%); (G2) cerebelo em 2/30 (6,6%); (G3) supratentoriais associados a convulsões em 16/30 (53,3%) e (G4) supratentoriais sem convulsões em 7/30 (23,3%). Ressecção cirúrgica foi realizada em 26 de 30 (86,6%) pacientes, com seguimento médio de 4,1 anos. De 15 crianças com convulsões pré-operatórias, todas ficaram livres das crises após a cirurgia. Conclusões:Para angioma cavernoso intracraniano solitário e sintomático, o tratamento de escolha é excisão microcirúrgica total precedida de avaliação funcional e anatômica meticulosa. Para angiomas cavernosos intracranianos múltiplos ou pacientes assintomáticos, as modalidades terapêuticas devem ser consideradas cautelosamente.